2017
DOI: 10.1007/s40544-017-0191-5
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemistry aspects on frictional interfaces

Abstract: Friction exists wherever relative motion occurs and is the main source of energy consumption. Lubrication plays a significant role in improving fuel efficiency, reducing emissions, and prolonging the service life of machines. Surface interactions between two moving solid surfaces or the flow of a fluid (and/or environment) on a solid surface are the primary causes of friction. Apart from the mechanical design of moving parts, surface physicochemistry is of crucial importance to lubrication. This review deals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 112 publications
(142 reference statements)
0
19
0
Order By: Relevance
“…In modern industry, reducing friction and wear plays a significant role in improving mechanical components' durability and efficiency. The oil-based lubricants are widely used in industries to make machines run more effectively (Cai et al , 2017). However, with the development of technology, the oil alone cannot meet the lubrication requirements of mechanical equipment under severe working conditions, such as heavy load, high speed and high temperature (Niu et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In modern industry, reducing friction and wear plays a significant role in improving mechanical components' durability and efficiency. The oil-based lubricants are widely used in industries to make machines run more effectively (Cai et al , 2017). However, with the development of technology, the oil alone cannot meet the lubrication requirements of mechanical equipment under severe working conditions, such as heavy load, high speed and high temperature (Niu et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These problems caused by friction are particularly important in nanometer-sized devices and machines because of the high surface-to-volume ratio of nanostructures. Two-dimensional (2D) materials [3][4][5], such as graphene [6] and molybdenum disulfide (MoS 2 ) [7,8] can considerably reduce the wear and friction in mechanical systems, owing to their chemical inertness [9][10][11][12], high strength [13], and peculiar structure [14]. For example, Kawai et al discovered ultra-low friction between graphene nanoribbons and an Au surface [15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the lubricant employing ILs as additives in base oils boosts the lubricating efficiency and reduces the cost to increase their potential applicability at industrial scales [4,8,[17][18][19][20]. A phosphonium-based IL adding into the hydrocarbon oil with an IL concentration of 5 wt%, has demonstrated a significant reduction in the friction coefficient in steel-cast iron contacts [21].…”
Section: Introductionmentioning
confidence: 99%